DESKRIPSI PETANI KAKAO DALAM MEMENUHI KEBUTUHAN POKOK MINIMUM - Dwi Puastuti; Budiyono Budiyono; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2013)
The objective of this research is to gain the representation about the efforts of fulfilling the needs for cacao’s family members at Banyumas, Pringsewu year 2012. The pressure points of this research are on number of children; quality of responsibility, large of the field, cacao production, income level, and minimum fulfillment needs level of cacao’s farmers. This research uses description methodology. The population was 181 patriarchs. The taken sample was 25% of 45% patriarchs. The researcher used three data collecting techniques; they were observation, questioner interview, and documentation. Qualitative percentage data analysis was in form of single table. The result of the research is shown that: (1) there are 88,67% cacao’s farmers who have more than three children, (2) there are 57,77% cacao’s farmers have responsibility for more than five persons,(3) there are 44,44% cacao’s farmers have middle large field (0,50-0,99 ha), (4) there are 88,88% which had been produced above 1000 kg/ha, (5) there are 86,67% cacao’s farmers income got ≤Rp. 855.000, (6) there are 80% fulfillment needs which can be reached